國中小校長學習領導、教師學習領導及學生核心素養關係之研究：素養導向教育觀點 A Study on the Correlations Among Elementary and Junior High School Principal Leadership for Learning, Teacher Leadership for Learning, and Student Core Competency: Perspective of Competency-Based Education - 簡瑋成 Wei-Cheng Chien (National Taiwan Normal University, 2022)
十二年國民基本教育揭示對學生核心素養培育之重視，掀起國內素養導向教育之改革浪潮，因此如何提升學生素養能力的學校領導成為重要研究議題，這當中又以學習領導最接近此教育理念。此外，在過去幾十年中，領導力理論開始重視校長和教師領導力的相互作用，以及探討對學生學習表現之間的聯繫，但這其中的關聯性研究仍存在著巨大的研究斷層。因此，本研究致力於探討校長與教師的學習領導對學生核心素養之影響關係，以此瞭解從校長、教師到學生一連串的素養導向教育之關係。研究採用線上匿名問卷調查全國國民中小學教師，最後回收有效問卷1,490份，經統計分析獲得以下結論：一、國民中小學校長學習領導是十二年國民基本教育素養導向教育的重要推手；二、國民中小學校長學習領導在教師學習領 導方面具有顯著的高度正向直接影響；三、國民中小學校長學習領導對學生核心素養具有顯著的中低度正向直接影響；四、國民中小學教師學習領導對學生核心素養具有顯著的高度正向直接影響；五、國民中小學校長學習領導經由教師學習領導，在學生核心素養方面具有顯著的中度正向中介影響。 Research Motivation and Purpose Taiwan's 12-year basic education curriculum initiated a wave of reform in domestic competency-based education. Therefore, the enhancement of school leadership for student competency has become a key research topic. Leadership for learning is particularly relevant to these research developments. Leadership theories formulated in the past few decades center on the relationship between principal and teacher leadership and their influence on student performance. However, a research gap still exists in this area. This study explores the influence of principal and teacher leadership for learning on student core competency. This investigation reports a series of competency-based correlations involving principals, teachers, and students. Literature The ultimate goal of school-based education is the enhancement of student learning outcomes, and principal and teacher leadership should be directed toward this end. The joint investigation of principal and teacher leadership to understand their influence on school processes and student performance is central to modern school leadership research (e.g., Hallinger & Heck, 2010; Heck & Hallinger, 2009; Leithwood & Mascall, 2008; Louis et al., 2010; Spillane, 2006). These studies have primarily discussed the crucial influence of principal and teacher leadership on student learning and describe the intermediary role of teacher leadership. For example, Sebastian et al. (2017) studied the relationship of principal leadership with that of teachers to observe its influence on student performance; thus, they elucidated both the direct and indirect effects of leadership on student achievement. Their results indicated that principal leadership influences students in two respects. First, teacher leadership mediates this influence on students, and, second, teacher leadership mediates the influences of principal and teacher leadership on student performance. Another study by Sebastian et al. (2016) also reported that teacher leadership plays a key intermediary role between principal leadership and student achievement. . Methods The subjects of the study were teachers of elementary and junior high schools in Taiwan, and the survey was conducted by means of an online anonymous questionnaire. 200 schools were randomly selected, and the selected schools were requested to send the online anonymous questionnaire URL to all teachers of the school. A total of 1,615 questionnaires were recovered, including invalid questionnaires. After deducting invalid questionnaires, 1,490 valid questionnaires were finally recovered, and the effective rate of questionnaire recovery was 92.26%. Results and Discussion (1) According to survey results, participants had a moderate to high level of principal and teacher leadership in relation to learning and a moderate level of student core competency. Principal leadership for learning scores were the highest , indicating that principals were most influential in developing competency-based education. (2) Most studies have reported a low to nonsignificant direct influence of principal leadership on student learning (Bryk et al., 2010; Witziers et al., 2003); this is consistent with the low level of influence reported in this study. (3) This study found that teacher leadership for learning has a highly positive and direct influence on student core competency. The results of this study are consistent with those reported in the literature on teacher leadership. The primary purpose of teacher leadership is to strengthen the leadership behaviors for students to enhance learning effectiveness (Childs-Bowen et al., 2000; Danielson, 2006; Zheng & Chen, 2013), and the ultimate goal is to improve student learning performance (Carpenter & Sherretz, 2012; Hanuscin et al., 2012; Hunzicker, 2012; Vernon-Dotson & Floyd, 2012). These same principles inform competency-based education. (4) This study demonstrates that principal leadership for learning moderately affects student core competency; this influence is mediated by teacher leadership for learning and is higher than the direct influence of principal leadership for learning on student core competency. These results indicate that principals must develop student core competency through teachers, consistent with the findings of Leithwood et al. (2010). Through the principal and teacher leadership, schools can influence student learning performance. Teacher leadership is a key intermediary between principal leadership and student learning (Sebastian et al., 2016; Sebastian et al., 2017). Conclusions (1) Elementary and junior high school principal leadership for learning is a key promoter of competency-based education in 12-year basic education. (2) Elementary and junior high school principal leadership for learning exhibits a significant, positive, and strong direct influence on teacher leadership for learning. (3) Elementary and junior high school principal leadership for learning exhibits a significant, positive, and moderate to low direct influence on student core competency. (4) Elementary and junior high school teacher leadership for learning exhibits a significant, positive, and strong direct influence on student core competency. (5) Elementary and junior high school principal leadership for learning, through teacher leadership for learning, exhibits a significant, positive, and moderate indirect influence on student core competency. Suggestions (1) Educational administrative agencies should develop the knowledge and ability of leadership for learning as part of the competency-based education of primary and middle school principals. (2) Principals of elementary and junior high schools should establish a competency-based education system and strengthen teachers' recognition and investment in the system. (3) Educational research units should develop a complete educational administrative database reporting the implementation status of competency-based education to be used by elementary and junior high schools for secondary data analysis.